2020
DOI: 10.3390/w12061585
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Transient Dynamics in a Bypass Reach

Abstract: The operating conditions of Nordic hydropower plants are expected to change in the coming years to work more in conjunction with intermittent power production, causing more frequent hydropeaking events. Hydropeaking has been shown to be detrimental to wildlife in the river reaches downstream of hydropower plants. In this work, we investigate how different possible future hydropeaking scenarios affect the water surface elevation dynamics in a bypass reach in the Ume River in northern Sweden. The river dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Similarly, it is observed that frequent sub-daily ramping dampens the dewatering effect far downstream in the river as the river starts rising again before the previous stop has reached the minimum level. A similar effect was seen by Burman et al (2020) running similar hydropeaking studies in a bypass reach in the Ume river in Sweden. The downstream effect of a hydropeaking operation in a river will be closely related to the ramping rate and longitudinal dampening in the river due to the morphology which has a large effect on dewatering rates (Hauer et al, 2014;Hauer et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, it is observed that frequent sub-daily ramping dampens the dewatering effect far downstream in the river as the river starts rising again before the previous stop has reached the minimum level. A similar effect was seen by Burman et al (2020) running similar hydropeaking studies in a bypass reach in the Ume river in Sweden. The downstream effect of a hydropeaking operation in a river will be closely related to the ramping rate and longitudinal dampening in the river due to the morphology which has a large effect on dewatering rates (Hauer et al, 2014;Hauer et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…An overview of the study reach in the proximity of Stornorrfors can be seen in Figure 1. The water level dynamics of the study reach was calibrated and validated for a hydropeaking cycle of 21 m 3 /s → 50 m 3 /s → 21 m 3 /s with a 5‐min flow change time in a previous study (Burman et al, 2020). The well‐defined flow conditions as well as validation data from previous work (Andersson et al, 2012; Angele & Andersson, 2018; Burman et al, 2020) performed in the reach made it a suitable study site.…”
Section: Methodsmentioning
confidence: 99%
“…One such effect, the hysteresis in the increase-decrease cycle causes, likely adds additional spikes to the spectrum. The hysteresis in turn depends on 3D effects, such as turbulence, as well as longitudinal distance from the spillways (Burman et al, 2020).…”
Section: Fourier Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the influence of the flow rate in the old river channel on the preferences for the fish in a biotope perspective, a biological and hydraulic field investigation was made, Angele [2]. A 2D transient, hydraulic model using Hydraulic Engineering Center River Analysis System (HEC-RAS) was also conducted, see also Burman [10], in which different flow scenarios were tested. The conclusion was that the fish preferences in terms of local water velocity and water depth were optimized for a flow rate of 10 m 3 /s in the old river channel.…”
Section: Figurementioning
confidence: 99%